Measures for clinical practice and research : couples, families, and children - Corcoran, Kevin; Fischer, Joel (New York : Oxford University Press, 2007)
Contenido: Measurement and practice. Basic principles of measurement. Types of measurement tools. Advantages and disadvantages of rapid assessment instruments. Selecting measures for practice. Administering the instruments. Instruments for practice and research. Instruments for couples. Instruments for families. Instruments for children.